2019
DOI: 10.1186/s12992-019-0453-2
|View full text |Cite
|
Sign up to set email alerts
|

The health impacts of extractive industry transnational corporations: a study of Rio Tinto in Australia and Southern Africa

Abstract: Background Operations of transnational corporations (TNCs) affect population health through production methods, shaping social determinants of health, or by influencing regulation of their activities. Research on community exposures to TNC practices and policies has been limited. Our research on extractive industries examined Rio Tinto in Australia and Southern Africa to test methods for assessing the health impacts of corporates in high and middle income jurisdictions with different regulatory fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 50 publications
(51 reference statements)
3
24
0
Order By: Relevance
“…Indeed, recurrent thematic aspects reported in our study have been studied in previous research, including environmental [ 14 , 15 ], social [ 18 , 39 ] or economic [ 10 , 35 , 40 ] determinants of health. While several studies report potential health benefits [ 10 , 41 ], negative aspects tend to prevail in studies synthesising health literature [ 18 , 42 , 43 ], which is in line with our findings. Similarly, a recent study have reported a positive trend of water infrastructure in mining regions but health benefits were less evident [ 44 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, recurrent thematic aspects reported in our study have been studied in previous research, including environmental [ 14 , 15 ], social [ 18 , 39 ] or economic [ 10 , 35 , 40 ] determinants of health. While several studies report potential health benefits [ 10 , 41 ], negative aspects tend to prevail in studies synthesising health literature [ 18 , 42 , 43 ], which is in line with our findings. Similarly, a recent study have reported a positive trend of water infrastructure in mining regions but health benefits were less evident [ 44 ].…”
Section: Discussionsupporting
confidence: 92%
“…Studies measuring health conditions of local communities [e.g. 10 , 41 , 45 ] might have missed important aspects for the health and well-being as perceived by affected populations themselves. For example, health effects caused by cracks in the houses related to blasting and cultural dimensions of health have to our best knowledge received little attention.…”
Section: Discussionmentioning
confidence: 99%
“…Even though extractive industries may contribute to improved health outcomes locally through improved public infrastructures, employment and business opportunities, these effects are likely to be too small to be reflected in national estimates due to the relatively small populations directly exposed to such projects. From a central government perspective, natural resources are primarily of interest as a source of additional income, allowing governments to promote access to and improve quality of health services, along with socio-economic development more broadly [ 63 , 64 ] that can contribute to improved health outcomes [ 41 , 64 , 65 ]. Our results suggest that booms in global commodity prices do indeed create windfall revenue gains for governments in the short run.…”
Section: Discussionmentioning
confidence: 99%
“…Their model discusses the political, economic and regulatory environments; the structure, practices and products of corporations; and the health and equity impacts of the activities of corporations [13]. The authors later applied their model for an evaluation of the activities of a fast-food restaurant and a mining company [39,40]. Their findings showed that corporations could have a positive impact when providing employment in communities, for example, but this could be undermined by the precariousness of such employment, and the negative impacts of the company's activities on the environment and health [39,40].…”
Section: Corporations and Practices Harmful To Healthmentioning
confidence: 99%
“…The authors later applied their model for an evaluation of the activities of a fast-food restaurant and a mining company [ 39 , 40 ]. Their findings showed that corporations could have a positive impact when providing employment in communities, for example, but this could be undermined by the precariousness of such employment, and the negative impacts of the company’s activities on the environment and health [ 39 , 40 ]. It has been noted that the Baum et al model, however, fails to address some corporate practices, such as the influence of businesses on science and social norms [ 12 ].…”
Section: The Commercial Determinants Of Healthmentioning
confidence: 99%